2014
DOI: 10.7554/elife.03765
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin-controlled spatial decoding of oscillatory Ca2+ signals by calcineurin

Abstract: Calcineurin is responsible for mediating a wide variety of cellular processes in response to dynamic calcium (Ca2+) signals, yet the precise mechanisms involved in the spatiotemporal control of calcineurin signaling are poorly understood. Here, we use genetically encoded fluorescent biosensors to directly probe the role of cytosolic Ca2+ oscillations in modulating calcineurin activity dynamics in insulin-secreting MIN6 β-cells. We show that Ca2+ oscillations induce distinct temporal patterns of calcineurin act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 106 publications
(157 reference statements)
6
75
0
Order By: Relevance
“…The CaNAR reporter is based on the regulatory domain of NFAT tagged on opposing ends with a cyan and a yellow fluorescent protein. Dephosphorylation by calcineurin causes a conformational change that increases FRET transfer between the two ends [17]. This can be combined with a Ca 2+ sensor to integrate Ca 2+ dynamics with processing of a specific calcineurin substrate.…”
Section: Methods For Measuring Calcineurin Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…The CaNAR reporter is based on the regulatory domain of NFAT tagged on opposing ends with a cyan and a yellow fluorescent protein. Dephosphorylation by calcineurin causes a conformational change that increases FRET transfer between the two ends [17]. This can be combined with a Ca 2+ sensor to integrate Ca 2+ dynamics with processing of a specific calcineurin substrate.…”
Section: Methods For Measuring Calcineurin Activitymentioning
confidence: 99%
“…This can be combined with a Ca 2+ sensor to integrate Ca 2+ dynamics with processing of a specific calcineurin substrate. Targeting this reporter to the cytosol, plasma membrane, mitochondria, or the ER, has been used to demonstrate that activation of the reporter in response to the same Ca 2+ signal can be very different in different regions of a cell [17]. For instance, in a pancreatic β cell line, the cytoplasmic and plasma membrane reporter displayed a single, integrated response to an oscillatory Ca 2+ input.…”
Section: Methods For Measuring Calcineurin Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the amplitude and the frequency as well as the spatial distribution (see below) of calcium oscillations may encode a specific downstream response [85]. For example, activation of calcineurin in an insulin-producing cell line has been demonstrated to be controlled by calmodulin in a way that allows oscillatory signals to generate specific functional outputs within different cellular compartments [86]. Furthermore, it has recently been shown that different isoforms of the transcription factor NFAT are specifically activated by distinct patterns of calcium signals [87].…”
Section: Mechanisms and Kinetics Of Receptor Activationmentioning
confidence: 99%